Effect of Recondition of Fracture Shaft Palm Lorry Using The Shielded Metal Arc Welding Process - Hakim Nasution, Lukman; Eka Ariefyanto Putra; Gapar; Fajar Budiman; Rama Yoedha Satria; Andersen; Sofyan Hadi; Ferry Adriyan; Nasrol Akmal; Rinaldi; Nazaruddin; Safril Safar; Heri Suripto (Aptek, 2024)
Examination and analysis of the 2,640 working hours AISI 1045 palm lorry shaft fracture were carried out to determine the effect of reconditioning using Shielded Metal Arc Welding on the reliability of the shaft. Laboratory test results and analysis showed that the shaft experienced a static brittle fracture at an angle between 65 mm diameter and 90 mm diameter. For a long time, evidence of weld defects in the form of inclusions, porosity, and cold cracks in the Heat Affective Zone has been observed. The various hardness levels in the weld metal are 200 to 210 HV; HAZ is 280 to 386 HV, and base metal is 202 to 210 HV due to oxygen affecting on shaft's mechanical qualities deterioration. When the martensitic structure is produced, the carbon equivalent value rises to 15.66%, over the minimum value of 0.65%, reducing shaft reliability and triggering the occurrence of static brittle fracture. The macro-micro structure at the initial area of crack and fracture is bainite and ferrite-pearlite, while the shaft base material is ferrite-pearlite. Furthermore, there is a difference in tensile strength between the shaft material and the power of the electrodes utilized in the reconditioning process. From this experiment, the recondition